2016
DOI: 10.1097/apo.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Myopia

Abstract: Myopia is not a simple refractive error, but an eyesight-threatening disease. There is a high prevalence of myopia, 80% to 90%, in young adults in East Asia; myopia has become the leading cause of blindness in this area. As the myopic population increases globally, the severity of its impact is predicted. Approximately one fifth of the myopic population has high myopia (≥-6 diopters), which results in irreversible vision loss such as retinal detachment, choroidal neovascularization, cataracts, glaucoma, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
213
2
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(239 citation statements)
references
References 135 publications
5
213
2
19
Order By: Relevance
“…The odds of having combined refractive errors and myopia alone were twice as high among urban children compared to rural children. This is similar to earlier findings on the epidemiology of refractive error in other parts of the world and this meta‐analysis provides further support for this pattern across India. This may be due to the increased educational demands leading to more near vision activities .…”
Section: Discussionmentioning
confidence: 99%
“…The odds of having combined refractive errors and myopia alone were twice as high among urban children compared to rural children. This is similar to earlier findings on the epidemiology of refractive error in other parts of the world and this meta‐analysis provides further support for this pattern across India. This may be due to the increased educational demands leading to more near vision activities .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the individual relationship of digital screen time as a risk factor for myopia. However, consistent evidence of an association between screen time and myopia development is lacking . Education and near work have played major roles in the rise in myopia rates even before the introduction of digital devices .…”
Section: Introductionmentioning
confidence: 99%
“…From 350 BC to now, literature has showed hypotheses about etiology of myopia such as lack of enough outdoor activities and too long time of near work 1 , literature suggested that blue light from screen may correlate with myopia 3,4 , but the identical effect of blue light remains unclear [3][4][5] . The specific causes of myopia remain undefined 1,6,7 .…”
Section: Textmentioning
confidence: 99%
“…1. k). 4. Taking the distance of S for example, the S is the furthest vision distance for the three chosen visual light photons for the health eye.…”
Section: A Hypothesis Of Massive Photons Of High-frequency Electromagmentioning
confidence: 99%